WASTE MATERIAL RATIO ANALYSIS OF REBAR USING THE BIM METHOD IN CONSTRUCTION DESIGN AND BUILD - Fachreza Alyazid Athar Nugraha; Ryan Faza Prasetyo (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2024)
Construction of the Taman Mini Indonesia Indah Parking Building project is conducted by using a design-build procurement system. During its implementation, 36 changes were made to the working drawings for the ground structure. This was due to the existing ground conditions and changes in space allocation at the client’s request. Objectives: This research aims to compare the waste of reinforcement materials that can occur between conventional methods and BIM methods, particularly in the design work. Methodology and results: In order to be able to calculate the volume of iron material using BIM, working drawing data was collected. In addition, an interview was conducted with the contractor to obtain detailed information on the revised working drawings. The BIM method of calculating the volume of material is carried out using the supporting software Autodesk Revit. Conclusion, Significance, and implications: The results showed that the waste material ratio value of the BIM method was higher than the conventional method with the results in the conventional method is 4.83% and in the BIM method is 6.58%. These results contribute to the development of material waste evaluation, especially in the type of design project. However, previous research that has been conducted focuses more on the type of construction project only.